An amygdala‐centered hyper‐connectivity signature of threatening face processing predicts anxiety in youths with autism spectrum conditions. Issue 11 (23rd August 2021) - Chen, Yu‐Chun; Chen, Chenyi; Martínez, Róger Marcelo; Fan, Yang‐Tang; Liu, Chia‐Chien; Chen, Chin‐Yau; Cheng, Yawei
Abstract: Anxiety is exceedingly prevalent among individuals with an autism spectrum condition (ASC). While recent literature postulates anxiety as a mechanism encompassing an underlying amygdala‐related elevated baseline level of arousal even to nonthreatening cues, whether this same mechanism contributes to anxiety in those with an ASC and supports the transdiagnostic nature of anxiety remains elusive. In this case–control study of 51 youths (26 ASC), we assessed autism and anxiety via the Autism‐Spectrum Quotient and the State–Trait Anxiety Inventory, respectively. Hemodynamic responses, including amygdala reactivity, to explicit and implicit (backwardly masked) perception of threatening faces were acquired using functional Magnetic Resonance Imaging (fMRI). For explicit fear, ASC individuals showed significantly greater negative correlations between the amygdala and the attentional deployment‐parietal network. For implicit fear, ASC individuals showed significantly stronger correlations of the amygdala with the prefrontal networks, temporal pole, and hippocampus. Additionally, an fMRI‐based neurologic signature for anxiety in ASCs was identified via the LibSVM machine learning model using amygdala‐centered functional connectivity during the emotional processing of explicit and implicit stimuli. Hypervigilance to implicit threat in ASCs comorbid with anxiety might exacerbate explicit threat reactivity; hence the use of attentional avoidance patterns to restrict affective hyperarousal for explicitly perceived socioemotional stimuli. Consequently, developing an attention‐independent behavioral/neural marker identifying anxiety in ASCs is highly warranted. Lay Summary: This study identifies a dissociation of amygdala reactivity dependent on explicit and implicit threat processing. Implicit anxiety in individuals with an autism spectrum condition (ASC) could outweigh explicitly induced threat. When explicitly perceiving socioemotional stimuli, ASC individuals with anxiety might use attentional avoidance patterns to restrict affective hyperarousal.